Exploring lecturers and administrative staffs’ strategies to hone EFL students’ digital literacy - Febriyantina Istiara; Tommy Hastomo (JOALL (Journal of Applied Linguistics and Literature), 2023)
This study seeks to investigate the strategies used by college teachers and administrators in enhancing the digital literacy skills of EFL students. A qualitative study is the research design in this paper. The researchers chose a purposive sampling technique for administering the research sample. There were six EFL lecturers and six higher education admins at STKIP PGRI Bandar Lampung as the research sample. This present research employed semi-structured interviews for collecting the data. This current study analyzed the data qualitatively and described it thematically. The findings illustrated that the lecturer used four strategies for promoting learners' digital literacy; motivate learners, conduct training workshops, employ digital technology in the classroom, and improve the digital classroom environment. Moreover, higher education admins used four strategies; raise guardians' awareness towards the role of digital technology, conduct training for lecturers and learners, redesign the EFL classroom and enhance classroom infrastructure. This finding implies that policymakers can use this research to plan and make a new system for EFL education.